Association Between Platelet Count and Liver Enzymes in Critical Phase Dengue Patients: A Cross-Sectional Study - Maria M Barek Teluma; Nur Ismi; Andi Heriadi Palloge (Edukasi Ilmiah Indonesia, 2026)
Introduction: Dengue infection remains a major cause of hospitalization in tropical regions, particularly during the critical phase when plasma leakage, thrombocytopenia, and organ involvement increase the risk of severe complications. Hepatic dysfunction, reflected by elevated aspartate aminotransferase (AST) and alanine aminotransferase (ALT), frequently accompanies hematologic deterioration. However, the phase-specific association between platelet count and liver enzyme elevation remains insufficiently characterized. This study aimed to determine the association between platelet count and AST and ALT levels among patients in the critical phase of dengue infection. Research Methodology: An analytic observational study with a cross-sectional design was conducted at Dr. TC Hillers Regional General Hospital, East Nusa Tenggara, Indonesia, between January and December 2025. A total of 68 patients meeting the WHO criteria for critical-phase dengue were included through consecutive sampling. Platelet count, AST, and ALT levels were extracted from medical records. Data distribution was assessed using the Shapiro–Wilk test. Pearson or Spearman correlation analysis was applied as appropriate. Statistical significance was set at α = 0.05. Results: The mean platelet count was 72.4 ± 28.7 ×10³/µL. Mean AST and ALT levels were 148.6 ± 64.2 U/L and 96.3 ± 41.8 U/L, respectively. Elevated AST was observed in 95.6% of patients, and elevated ALT in 85.3%. A significant negative correlation was found between platelet count and AST (r = −0.412, p = 0.001) and between platelet count and ALT (r = −0.356, p = 0.003). Conclusion: Platelet decline is significantly associated with hepatic enzyme elevation during the critical phase of dengue infection. Integrated monitoring of platelet counts and transaminases may enhance risk stratification and support early identification of severe systemic involvement in endemic hospital settings.